Large geomagnetically induced currents at equator caused by an interplanetary magnetic cloud - Nilam,B.; Tulasiram,S. (My University, 2022)
Here, we report a rare observation of an extremely large and rapid change of geomagnetic field (dB/dt), a proxy for the geomagnetically induced currents (GICs), at the equator caused by a sudden drop in solar wind density at the front boundary of a magnetic cloud (MC) during the great 31 March 2001 storm. The horizontal component at the Indian equatorial station, Tirunelveli, recorded a sharp decline of ∼350 nT in just 5 min with a peak dB/dt exhibiting a concerning value of 136 nT/min, a possible GIC risk to the electric power systems. The responsible physical mechanisms were examined through magneto-hydrodynamic model simulations and found that a prompt penetration of strong westward-overshielding electric fields and ionospheric currents at the equator play a dominant role. This study provides some new insights into the extent of extreme geomagnetic field changes that can occur at the equatorial region due to solar wind density reduction at MC, which can have potential impacts on the electric power grid systems. Plain Language Summary: The Earth, a planet with an intrinsic magnetic field bubble around it, is immersed in a hot and energetic solar wind plasma that continuously emanated from the Sun. The sudden disturbances on the Sun, such as coronal mass ejections, induce transient structures in the solar wind which, when directed earthward, can cause severe disturbances in the Earth's (Geo) magnetic field. The rapid changes in the geomagnetic field induce electric fields at the conducting surface of Earth, which can cause strong electrical currents, known as geomagnetically induced currents (GICs), that flow through the long conducting structures, like electric power transmission lines, long pipelines, etc., on the ground. The enhanced GICs are of serious threat to the electric power and pipeline grids. The elevated GICs are most popularly known to occur at high latitudes during severe geomagnetic storms. This study reports a rare observation of a large and rapid change in geomagnetic field indicating the strong GICs at the geomagnetic equator due to a magnetic cloud structure in solar wind and reveals the underlying physical processes.
Keywords: Magnetic cloud; Sudden impulse; Geomagnetically Induced Current; GICs; Equatorial Electrojet